Social Environment as a Source of Learning on Subjects Social Sciences - Pinoa, Wiclif Sepnath; Far, Gazali Far; Pattiasina, Johan (IJECA (International Journal of Education and Curriculum Application), 2022)
The social environment is a combination of individuals and groups that always display different activities and characters. Many things are always displayed in the community, but only pass by. This research aims to see the existence of the social environment around students to support the IPS learning process. Because the field of study IPS is an integrated subject consisting of several studies, namely history, geography, economics, and to. The research method used in this research is library research. With data sources of books, journals, and articles that have relevance to the topic under study. With research techniques, first, the selection of topics based on problem identification; second, exploration of information, looking for sources; third, determination of the focus of research based on information; fourth, data sources, in the form of information or data from books, journals, articles; Fifth, read sources, read and study sources critically to achieve maximum results. sixth, make research notes, which is arguably the most important stage and may also be the culmination of the entire series of research; seventh, the researcher makes notes related to the source that has been read to be processed/analyzed to obtain conclusions; Eighth, the researcher compiled the final report.The results showed that the use of the community environment as a learning resource is very relevant in IPS subjects. Because the community environment is always related to historical, socio-cultural, economic, and geographical issues.